Teaching quality counts: how student outcomes relate to quality of teaching in private and public schools in India - Singh, R; Sarkar, S (Young Lives, 2012)
This mixed-methods paper investigates whether the ‘private school premium’, as manifested in student learning outcomes, is the result of better-quality teaching in private schools. Using school-, community- and household-level data from the Young Lives longitudinal study in the state of Andhra Pradesh in India, this paper makes a detailed comparison of 227 government and private schools attended by the children in the sample. The results from our regression analysis suggest that privately educated children have a significantly higher (at 1 per cent) mathematics score than children in government schools. While characteristics of teachers like experience, gender, content knowledge and subject specialisation do not have any significant influence on children’s learning outcome, teaching practices like regularly checking homework and factors such as the proximity of the teacher's residence to the school and teachers’ attitude towards the children, as well as teachers’ perceptions of their schools, have emerged as important determinants. In short, it is what the teacher ‘believes and does’ in the classroom that has the maximum impact on children’s learning outcomes. Another key finding is that the students of teachers with professional qualifications have significantly higher outcomes (at 10 per cent in value-added specification) than children taught by teachers with only senior secondary education. But students of teachers with degrees in Education do not have significantly better outcomes than those taught by teachers with general degrees, after controlling for other factors. This has significant implications for policy on teacher recruitment and pre-service teacher training, as well as the development of regulatory frameworks. Setting standards for teaching and learning, to create appropriate benchmarks for both government and private schools, should be addressed as a matter of urgency.